Comparison of package inserts and patient information leaflets: an in-depth analysis of prescribing information in angiotensin receptor blockers marketed in South Africa - Aziz, Zainab (My University, 2017)
Lack of information has been identified as a major factor as to why patients do not take their medicines as the prescriber intends. Provision of appropriate information in a suitable form is therefore crucial. The package insert (PI) is the document that ensures the safe and effective use of the medicine under most circumstances. It presents a scientific, objective account of the medicine’s use as established by pre-clinical, clinical and often post-marketing studies. The patient information leaflet (PIL), which contains information for the consumer should be less scientific. South African legislation states that information contained in PILs must be aligned to PIs but the text must be readily intelligible for the patient. The study included a detailed comparison of prescribing information contained in the PI compared to the PIL in selected Angiotensin Receptor Blockers (ARBs). Findings of this comparative analysis revealed that key safety information was omitted from the PILs. An evaluation of the readability of the PILs was also performed by the use of Fry’s readability formula as well as applying elements of critical discourse analysis to determine if the texts in the PILs are suitable for its purpose. The results of the Fry’s readability assessments of all the PILs indicated that they had exceeded the recommended grade 7 reading level, which is in line with the adult literacy rate that qualifies anyone older than 15 years with a grade 7 qualification as being literate. Findings from the critical discourse analysis of the PILs show frequent use of medical jargon, complex sentence construction as well as ambiguity and slippage in the meaning of the texts in the PILs. The texts are not patient-friendly. Overall, the findings from this study indicate an urgent need to address the poor construction of PILs, to ensure that patients receive appropriate written prescribing information. This will ultimately ensure the safe and effective use of the medicine.
A research report submitted to the Faculty of Health Sciences, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science (MSc) in Pharmaceutical Affairs.
Keywords: Receptors, Angiotensin; Product Labeling